Phenothiazine-based multifunctional fluorescent probe for one-site rapid detection of hydrazine in cells, soil, water samples and test strip. (May 2023) - Huang, Yongfei; Liang, Junping; Fan, Zhefeng
Abstract: Hydrazine is widely used as a wide range of industrial chemical reagents. Because of its toxicity and explosiveness, it poses a serious threat to human health and ecological security. Therefore, it is of great significance to develop a real-time tracing method for hydrazine. Here, a novel turn-on fluorescent probe SXNU-1 for the detection of hydrazine was synthesized based on phenothiazine. SXNU-1 showed excellent selectivity toward hydrazine over various competitive species. Vinyl group with cyano and ethylacetate groups in SXNU-1 could react with hydrazine to form Schiff's base, showing bright green fluorescence. The response mechanism was verified by theoretical calculation, 1 H NMR titration and HRMS. In addition, SXNU-1 can determine hydrazine in soil, water samples and test strip. Because SXNU-1 has good cell membrane permeability, it can monitor different concentrations of hydrazine in HeLa cells. Therefore, we believe that SXNU-1 has great potential in the analysis and monitoring of environmental pollutants. Graphical abstract: Image 1 Highlights: Phenothiazine-based multifunctional fluorescent probe was synthesized by a simple condensation reaction. The probe showed high selectivity and fast response to hydrazine in DMSO/PBS (1/1, v/v, pH = 7.4) system. The probe with excellent performance showed good applications in cells, soil, water samples and test strip detection.